Advances in Fecal Microbiota Transplantation for Gut Dysbiosis‐Related Diseases - Shuna Hou; Jiachen Yu; Yongshuang Li; Duoyi Zhao; Zhiyu Zhang (Advanced Science)
Abstract This article provides an overview of the advancements in the application of fecal microbiota transplantation (FMT) in treating diseases related to intestinal dysbiosis. FMT involves the transfer of healthy donor fecal microbiota into the patient's body, aiming to restore the balance of intestinal microbiota and thereby treat a variety of intestinal diseases such as recurrent Clostridioides difficile infection (rCDI), inflammatory bowel disease (IBD), constipation, short bowel syndrome (SBS), and irritable bowel syndrome (IBS). While FMT has shown high efficacy in the treatment of rCDI, further research is needed for its application in other chronic conditions. This article elaborates on the application of FMT in intestinal diseases and the mechanisms of intestinal dysbiosis, as well as discusses key factors influencing the effectiveness of FMT, including donor selection, recipient characteristics, treatment protocols, and methods for assessing microbiota. Additionally, it emphasizes the key to successful FMT. Future research should focus on optimizing the FMT process to ensure long‐term safety and explore the potential application of FMT in a broader range of medical conditions.